Residual toxicities and stomach poison effects of plant extracts to different stages of Colorado potato beetle [Leptinotarsa decemlineata Say (Coleoptera: Chrysomelidae)] - Cam, Halit; Gokce, Ayhan; Kadioglu, Izzet; Yanar, Yusuf; Demirtas, Ibrahim; Goren, Nezhun; Whalon, Mark E. (ENTOMOLOGICAL SOC TURKEY, EGE UNIV, 2012)
Residual toxicities and stomach poison effects of Hedera helix L., Reseda lutea L., Humulus lupulus L., Sambucus nigra L., Chenopodium album L., Solanum nigrum L. and Lolium temulentum L. against various stages of Colorado potato beetle were tested under laboratory conditions. All tested extracts caused some mortality to the beetle larvae. H.lupulus extract appeared to be the most toxic among the tested extracts for all stages, except the 4th instars and adults. In the second series of experiment, dose - response bioassay with H.lupulus against various stages of Colorado potato beetle were carried out. The calculated LC50 values were 66.6, 41.1 and 28.7 % (w/w) for the 1st, 2nd and 3rd instar larvae respectively. These results indicate that H.lupulus extract has a potential in control of Colorado potato beetle.
Keywords: Colorado potato betle; Leptinotarsa decemlineata; plant extract; residual toxicity; stomach poison; CHRYSOMELIDAE; COLEOPTERA; LARVAE; PESTS; Entomology